Localisation of HHV-8 in AIDS related lymphadenopathy. Issue 1 (1st February 2000) - O'Leary, J J; Kennedy, M; Luttich, K; Uhlmann, V; Silva, I; Russell, J; Sheils, O; Ring, M; Sweeney, M; Kenny, C; Bermingham, N; Martin, C; et al.
Abstract : Background —Many lymph node abnormalities have been described in AIDS. These include opportunistic infections that sometimes result in spindle cell pseudotumours, Kaposi's sarcoma (KS), malignant lymphoma (Hodgkin's and nonHodgkin's), and florid reactive hyperplasia. Among these, reactive hyperplasia is the most common manifestation of AIDS related lymphadenopathy. Aim —To examine whether human herpesvirus 8 (HHV-8), the aetiological agent of KS, can be localised in AIDS related lymphadenopathy and whether its appearance in such nodes is predictive of Kaposi's sarcoma development. Methods —A series of human immunodeficiency virus (HIV) positive men (n = 21) with AIDS related lymphadenopathy who at the time of presentation had KS or subsequently developed KS (n = 5) were examined. The prevalence of HHV-8 was assessed in these patients using solution phase polymerase chain reaction (PCR), real time TaqMan quantitative PCR, and in cell amplification techniques (PCR in situ hybridisation (PCR-ISH) and labelled primer driven in cell amplification). Results —Using standard solution phase PCR in a nested format, only two of the 21 patients with AIDS related lymphadenopathy were positive for HHV-8. The lymph node of one of these patients contained KS lesions. Three HHV-8 positive patients were identified using TaqMan PCR (the original two positive patients and one additional patient). All of the positive patients either subsequently developed KS (n = 2) or had KS at the time of diagnosis (n = 1). Two additional patients subsequently developed KS, but were negative for HHV-8 by solution phase PCR and TaqMan PCR. Using PCR-ISH, HHV-8 amplicons were identified in some lymphoid cells (in one patient) and in spindle cells of the KS lesion in another. The positive lymphoid cells were predominantly concentrated in B cell areas of the affected lymph nodes, confirming the B cell tropism exhibited by HHV-8. Conclusions —The presence of HHV-8 in AIDS related lymphadenopathy is predictive of KS development and probably represents seeding of HHV-8 infected B cells from the peripheral blood. These findings support a role for HHV-8 in the pathobiology of KS.